Unveiling Autonomy And Desire: A Psycho-Feminist Exploration Of Gertrude's Rebellion In D.H. Lawrence's Sons And Lovers (1913) (Journal of Namibian Studies : History Politics Culture, 2023)
This study investigates how a female subverts the traditional patriarchal view of women as passive objects of desire and how she pursues her own desires and makes choices that are not solely determined by male expectations in D.H Lawrence’s Sons and Lovers. The study is viewed through the lens of psycho-feminism. The chief argument of the study is that Gertrude is stuck in patriarchal chains. It is only her true efforts for empowerment and autonomy in societal norms that rebel against traditional gender roles, seeking independence and self-fulfillment. The study is qualitative by pursuing the character analysis of Gerturde. The study found that her unconventional behavior leads to conflicts within her family, affecting her relationships with her husband and children. The study also examined how Gertrude's journey towards autonomy and empowerment in Sons and Lovers is marked by a mixture of successes and failures. While she exhibits a strong will to defy societal norms and assert herself, her overbearing nature and romantic entanglements ultimately hinder her path to true autonomy and self-empowerment. The study contributes to a broader discussion on the impacts of gender roles on familial relationships.